The utility of heart-type free fatty-acid binding-protein (HFABP) levels for differentiating acute ischemic stroke from stroke mimics - AKOĞLU, HALDUN; SANRI, ERKMAN; KARACABEY, SİNAN; EFEOĞLU, MELİS; DENİZBAŞI ALTINOK, ARZU (My University, 2023)
Background: Heart-type fatty acid-binding protein (HFABP) is found in the myocardium, brain, and some organs and is rapidly released from damaged cells into the circulation in case of ischemia. Aims: We aimed to determine the diagnostic utility of HFABP levels in patients suggesting acute ischemic stroke (AIS). Methods: This study was a prospective, single-center, observational diagnostic accuracy study with a nested cohort design. The estimated sample size was 126 patients, with a 1:1 case and control ratio. We included all consecutive patients with a lateralizing symptom (motor or sensory) or finding suggesting AIS (139 patients) who presented to ED within 24 h of their symptom onset and collected plasma at admission to the ED. After further evaluations, 111 patients (79.8%) were diagnosed with AIS and 28 with other neurological diseases (stroke-mimics). Findings: In our study, the median HFABP levels of the cases and controls were 2.6 μg/ml and 2.2 μg/ml, respectively, without any statistically significant difference (p = 0.120). The diagnostic accuracy of HFABP for AIS was also insignificant at 0.60 (95% CI 0.51–0.68; p = 0.119). Discussion: Plasma HFABP level is not a marker that can differentiate AIS from other neurological pathologies in patients presenting to the ED, with findings suggesting AIS.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; CLINICAL NEUROLOGY; Nöroloji (klinik); Neurology (clinical); Diagnosis; Stroke; The heart-type fatty acid-binding protein